Understanding the interplay of compassion fatigue and moral resilience on moral distress in ICU nurses: a cross-sectional study - Yin, Jin; Zhao, Lili; Zhang, Na; Xia, Hui (Frontiers in Public Health, 2024)
Background Intensive Care Unit (ICU) nurses frequently confront significant psychological challenges, including compassion fatigue, moral distress, and diminished moral resilience. These issues not only affect their well-being but also impact the quality of care provided to patients. The interplay of these factors is complex and not fully understood, particularly how compassion fatigue influences the relationship between moral resilience and moral distress. Objectives To explore the complex interplay between compassion fatigue and moral distress among ICU nurses, and to elucidate how compassion fatigue influences the protective role of moral resilience against moral distress. Research design A cross-sectional study was conducted using a nationwide random sample of ICU nurses in China. Latent profile analysis identified subgroups based on levels of compassion fatigue. Moderation analysis examined whether compassion fatigue moderated the association between moral resilience and moral distress. Results Among 612 ICU nurses, latent profile analysis revealed three distinct groups with high, moderate, and low levels of compassion fatigue. Being female was protective against high compassion fatigue, while ages 30–49 yrs., lack of bachelor’s degree, and dissatisfaction with salary increased compassion fatigue risk. Moderation analysis showed compassion fatigue significantly moderated the relationship between moral resilience and moral distress. Nurses with higher compassion fatigue exhibited a stronger association between low moral resilience and high moral distress. Conclusion Compassion fatigue and moral distress are interconnected phenomena among ICU nurses. Demographic factors like gender, age, education, and income satisfaction impact compassion fatigue risk. High compassion fatigue impairs moral resilience, exacerbating moral distress. Comprehensive interventions targeting both compassion fatigue and moral resilience, tailored to nurses’ demographic profiles, are needed to support this workforce.